2023
DOI: 10.3390/ma16020741
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of ZnWO4/Carbon Black Nanocomposites Modified Glassy Carbon Electrode for Enhanced Electrochemical Determination of Ciprofloxacin in Environmental Water Samples

Abstract: The major problem facing humanity in the world right now is the sustainable provision of water and electricity. Therefore, it is essential to advance methods for the long-term elimination or removal of organic contaminants in the biosphere. Ciprofloxacin (CIP) is one of the most harmful pollutants affecting human health through improper industrial usage. In this study, a zinc tungsten oxide (ZnWO4) nanomaterial was prepared with a simple hydrothermal synthesis. The ZnWO4/Carbon black nanocomposites were fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…These electrodes were fabricated independently by the same procedure. This was evaluated by SWV responses for the oxidation of 10 μM CIP in N-prGO/CPE DPV 0.10-10 0.040 [61] ChCl/CPE SWV 0.005-200 0.004 [62] GO/SPCE DPV 1.0-8.0 0.300 [63] CNOs/PANI-NTs/GCE DPV 0.05-80.0 0.001 [15] ZnWO 4 /CB/GCE DPV 0.0-100 0.020 [64] Lu-Cu@h-BN/GCE SWV 0.05-100 0.030 This work 0.1 M PBS (pH 5.0) (Figure S6). The obtained RSD for the oxidation peak current responses was of 10 %, suggesting that the proposed sensor has an excellent reproducibility for the electro-oxidation of CIP.…”
Section: Selectivity Stability and Reproducibility Of Lu-cu@h-bn/gcementioning
confidence: 99%
“…These electrodes were fabricated independently by the same procedure. This was evaluated by SWV responses for the oxidation of 10 μM CIP in N-prGO/CPE DPV 0.10-10 0.040 [61] ChCl/CPE SWV 0.005-200 0.004 [62] GO/SPCE DPV 1.0-8.0 0.300 [63] CNOs/PANI-NTs/GCE DPV 0.05-80.0 0.001 [15] ZnWO 4 /CB/GCE DPV 0.0-100 0.020 [64] Lu-Cu@h-BN/GCE SWV 0.05-100 0.030 This work 0.1 M PBS (pH 5.0) (Figure S6). The obtained RSD for the oxidation peak current responses was of 10 %, suggesting that the proposed sensor has an excellent reproducibility for the electro-oxidation of CIP.…”
Section: Selectivity Stability and Reproducibility Of Lu-cu@h-bn/gcementioning
confidence: 99%
“…Several analytical techniques have been evolved for analyzing CFX as; some of analytical methods were summarized in the reported review [ 6 ], spectrophotometry [ 7 12 ], spectrofluorimetry [ 13 , 14 ], electrochemistry [ 15 – 17 ], high-performance liquid chromatography [ 18 20 ], capillary electrophoresis [ 21 ] and titration [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…[18] Taking this into consideration, recent research works have been reported concerning the advancement of electrochemical sensors designed for the detection of ciprofloxacin. Various electrode materials have been explored in these studies, including f-MWCNTs-Polydopamine, [19] reduced graphene oxide/poly(phenol red), [20] ZnWO 4 /carbon black nanocomposites, [21] nitrogen-doped porous reduced graphene oxide, [22] and a nanostructured lanthanum oxide interface substituted with reduced graphene oxide. [23] In a recent review, a succession of electroanalytical methodologies directed toward the detection of CF were exposed and documented by Crapnell et al, [24] demonstrating the resort to electrochemical sensors for the quantification of CF.…”
Section: Introductionmentioning
confidence: 99%